2015
DOI: 10.1038/mp.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

Lithium in the treatment of bipolar disorder: pharmacology and pharmacogenetics

Abstract: After decades of research, the mechanism of action of lithium in preventing recurrences of bipolar disorder remains only partially understood. Lithium research is complicated by absence of suitable animal models of bipolar disorder and by having to rely on in vitro studies of peripheral tissues. A number of distinct hypotheses emerged over the years, but none has been conclusively supported or rejected. The common theme emerging from pharmacological and genetic studies is that lithium affects multiple steps in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
166
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(172 citation statements)
references
References 165 publications
(167 reference statements)
6
166
0
Order By: Relevance
“…In addition, the role of lithium in the modulation of cell death and apoptosis has been previously suggested by several studies (Bielecka and Obuchowicz, 2008; Breen et al, 2016; Chiu and Chuang, 2010), although the role of specific genes in this mechanism still needs to be unraveled. Top signaling pathways that were suggested to underlie the anti-apoptotic properties of lithium include the modulation of the Wnt pathway (Hu et al, 2011), mitochondrial function and calcium homeostasis (Alda, 2015; Scola et al, 2014), the expression of anti-apoptotic proteins (Dwivedi and Zhang, 2014; Lowthert et al, 2012), neurotrophic factors (Dwivedi and Zhang, 2014; Emamghoreishi et al, 2015a; Hellweg et al, 2002), among others (Alda, 2015; Bielecka and Obuchowicz, 2008). Accordingly, a recent study has shown that lithium upregulates a gene module specific to apoptosis signaling and exert regulatory effects on apoptosis-controlling proteins involved in mitochondrial and endoplasmic reticulum function in LCLs from BD patients (Breen et al, 2016), which corroborates our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the role of lithium in the modulation of cell death and apoptosis has been previously suggested by several studies (Bielecka and Obuchowicz, 2008; Breen et al, 2016; Chiu and Chuang, 2010), although the role of specific genes in this mechanism still needs to be unraveled. Top signaling pathways that were suggested to underlie the anti-apoptotic properties of lithium include the modulation of the Wnt pathway (Hu et al, 2011), mitochondrial function and calcium homeostasis (Alda, 2015; Scola et al, 2014), the expression of anti-apoptotic proteins (Dwivedi and Zhang, 2014; Lowthert et al, 2012), neurotrophic factors (Dwivedi and Zhang, 2014; Emamghoreishi et al, 2015a; Hellweg et al, 2002), among others (Alda, 2015; Bielecka and Obuchowicz, 2008). Accordingly, a recent study has shown that lithium upregulates a gene module specific to apoptosis signaling and exert regulatory effects on apoptosis-controlling proteins involved in mitochondrial and endoplasmic reticulum function in LCLs from BD patients (Breen et al, 2016), which corroborates our findings.…”
Section: Discussionmentioning
confidence: 99%
“…This goes along with the increasing body of evidence suggesting a key role of pharmacogenetics in the response to lithium (Pisanu et al, 2016a). Accordingly, different, more homogeneous phenotypes have been identified within patients regarding their likelihood of showing an adequate response to lithium treatment (responders vs. nonresponders) (Geoffroy et al, 2017; Oedegaard et al, 2016; Scott et al, 2017; Sportiche et al, 2016), and the genetic basis of lithium responsiveness has been consistently shown by several studies (Alda, 2015; Alda et al, 2005; Grof et al, 2009; Grof et al, 2002; Hou et al, 2016). This is also supported by in vitro studies performed with LCLs, in which lithium has been shown to exert specific effects based on the donor’s treatment responsiveness (Hunsberger et al, 2015; Milanesi et al, 2015; Squassina et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a link between the action of Li on both acute and relapsing mood symptoms and its stabilization action of circadian rhythms has long been suggested in humans Klemfuss, 1992) and in rodents (Roybal et al, 2007). Li acts at a physiological level on the period, phase, amplitude and coupling of biological rhythms, and at a molecular level on circadian gene expression and protein production (Alda, 2015;Can et al, 2014;Kripke et al, 1979;Kripke and Wyborney, 1980a;Subramanian et al, 1998;Welsh and Moore-Ede, 1990;Yin et al, 2006). Further, Li appears to interact with environmental light through the retinalhypothalamic pineal pathway to influence circadian rhythms Pablos et al, 1994;Seggie et al, 1987;Werstiuk et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…1 This is especially true of lithium cation (Li + ), a trace metal of unknown biological function found in mammalian tissues at levels of 0.001-0.01 mM. [2][3][4][5] Li + is also of interest as a therapeutic to treat neurological diseases such as manic-depressive illness. However, dosage is critical, as Li + is only effective within a narrow therapeutic window (0.6-1.2 mM); too lower a dose has no effect while too higher a dose (>2 mM) is toxic and lethal.…”
Section: Introductionmentioning
confidence: 99%
“…However, dosage is critical, as Li + is only effective within a narrow therapeutic window (0.6-1.2 mM); too lower a dose has no effect while too higher a dose (>2 mM) is toxic and lethal. [1][2][3]6 Despite the importance of Li + in biology there are only a few reports of fluorescence-based sensors for its detection. 1, [6][7][8][9][10][11] Most of these are either non-functional at relevant biological concentrations, or they do not display sufficient selectivity over other metal cations, in particular Na + .…”
Section: Introductionmentioning
confidence: 99%